Successful Community Building in Alternative-Delivery Graduate Programs - Natasja Larson; Jim Parsons (Adult Education Research Conference, 2007)
This session discusses research that shows how community is created and enhanced in the University of Alberta Masters of Educational Studies (MES) graduate program. This hybrid program uses both on-line and face-to-face delivery. The discussion outlines findings from both open-ended survey results and collected notes from students.